Predictors Associated with the Curricular Performance of Student-Athletes in the Province of Pampanga, Philippines - Dominado , Noel L. (Progress in Language, Literature and Education Research Vol. 4, 2024)
In the education sector, sports are an important part of the curriculum at all levels because they help to develop the mental, physical, social, and emotional aspects of the pupils. This study was conducted to establish the potential association between predictors and curricular performance of student-athletes. To accomplish the reason for the study the descriptive research design was used. One hundred thirty-four athletes from the Province of Pampanga who competed in the Central Luzon Regional Association (CLRAA) in the School Year 2016-2017 served as respondents of the study. The sports involvement of student-athletes and its perceived effects on their curricular performance. For the physical aspect, sixty-six or 49.25% agreed the poor balanced diet, and seven, or 5.52% strongly disagreed that the injury acquired from sports involvement affected their curricular performance. On the other hand, regarding the social aspect, Seventy-four, or 55.22% agreed is teachers' discrimination was a factor that affected their curricular performance. While 11 or 8.20% strongly disagreed that discrimination from a classmate may effect their curricular performance. Likewise, in the emotional aspect, seventy individuals, or 52.23% disagreed Failure/defeat in sports involvement may result in a loss of Self-reliance. While six or 4.47% strongly agreed that defeats led to the loss of Courage. Lastly, mental aspect, fifty-nine individuals, or 44.02% agreed that the cause of anger often becomes the focus of attention. While eleven or 8.20% which were described strongly agreed is the worry. The result shows that there is no significant relationship between the factors and the curricular performance on the responses of student-athletes. There is a significant relationship between the athletes’ sports involvement and curricular performance.